2023
DOI: 10.32604/cmc.2023.034833
|View full text |Cite
|
Sign up to set email alerts
|

Application of Deep Learning to Production Forecasting in Intelligent Agricultural Product Supply Chain

Abstract: Production prediction is an important factor influencing the realization of an intelligent agricultural supply chain. In an Internet of Things (IoT) environment, accurate yield prediction is one of the prerequisites for achieving an efficient response in an intelligent agricultural supply chain. As an example, this study applied a conventional prediction method and deep learning prediction model to predict the yield of a characteristic regional fruit (the Shatian pomelo) in a comparative study. The root means … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…An intelligent FVSC is one that operates in an IoT environment and uses deep learning. Extant studies demonstrate that deep learning helps in classifying FV automatically and predicting supply and demand quantity to reduce food waste (Alharbi et al ., 2023; Chen et al ., 2022; Onoufriou et al ., 2023; Ya Ma et al ., 2023). ML prediction methods can be used in FV maturity forecasts by training on the data set acquired from the present and past scenarios to minimize food waste (Bouzembrak and Marvin, 2019; Croci et al ., 2022; Scalisi et al ., 2020).…”
Section: Results and Analysismentioning
confidence: 99%
“…An intelligent FVSC is one that operates in an IoT environment and uses deep learning. Extant studies demonstrate that deep learning helps in classifying FV automatically and predicting supply and demand quantity to reduce food waste (Alharbi et al ., 2023; Chen et al ., 2022; Onoufriou et al ., 2023; Ya Ma et al ., 2023). ML prediction methods can be used in FV maturity forecasts by training on the data set acquired from the present and past scenarios to minimize food waste (Bouzembrak and Marvin, 2019; Croci et al ., 2022; Scalisi et al ., 2020).…”
Section: Results and Analysismentioning
confidence: 99%
“…It has been found that maintaining higher safety stock levels necessitates the allocation of more resources and capital within the supply chain. Conversely, they also discovered that longer delivery lead-times were correlated with reduced safety stock levels, enabling businesses to better plan their inventory management and production processes (Ma et al, 2023).…”
Section: Literature Surveymentioning
confidence: 99%